Risk factors for neuromuscular complications in lower limbs after lung transplantation - Cho, Soomi; Lee, Jee Eun; Choi, Byeong Joo; Kim, Song Yee; Park, Moo Suk; Kim, Hyo-Hyun; Lee, Jin Gu; Paik, Hyo Chae; Shin, Ha Young; Kim, Seung Woo (Frontiers in Neurology, 2022)
Objective: This study aimed to analyze the prevalence and risk factors of neuromuscular complications after lung transplantation (LT), as well as the association between neuromuscular complications and extracorporeal membrane oxygenation (ECMO) support. Methods: We retrospectively included 201 patients who underwent LT between 2013 and 2020. Patients were classified into three groups based on the presence and the pattern of postoperative leg weakness: no weakness group, asymmetric weakness group, and symmetric weakness group. Comorbidities, duration of ECMO therapy, and postoperative complications were compared between the three groups. Results: Of the 201 recipients, 16 (8.0%) and 29 (14.4%) patients developed asymmetric and symmetric leg weakness, respectively. Foot drop was the main complaint in patients with asymmetric weakness. The presumed site of nerve injury in the asymmetric weakness group was the lumbosacral plexus in 8 (50%), peroneal nerve in 4 (25%), sciatic nerve in 2 (12.5%), and femoral nerve in 2 (12.5%) patients. In multivariate analysis, the use of preoperative ECMO was found to be independently associated with asymmetric weakness (OR, 3.590; 95% CI [1.227 – 10.502]). Symmetric leg weakness was associated with age at LT (1.062 [1.002 – 1.125]), diabetes mellitus (2.873 [1.037 – 7.965]), myositis (13.250 [2.179 – 80.584]), postoperative continuous renal replacement therapy (4.858 [1.538 – 15.350]), and duration of stay in the intensive care unit (1.052 [1.015 – 1.090]). Conclusion: More than 20% of patients developed leg weakness after LT. Early suspicion for peripheral neuropathy is required in patients after LT who used ECMO preoperatively, and who suffered from medical complications after LT.